Typification of the names published by Roberto de Visiani and Josif Pančić in Plantae Serbicae Rariores aut Novae—Decas I - Clementi, Moreno; Vukojičić, Snežana; Lakušić, Dmitar; Kuzmanović, Nevena (Phytotaxa, 2015)
We provide information on the typification of nine species names described by Roberto de Visiani and Josif Pančić in Plantae Serbicae Rariores aut Novae—Decas I, published in 1862. Seven lectotypes (Geum molle Vis. & Pančić, Potentilla lejocarpa Vis. & Pančić, P. visianii Pančić, Dianthus papillosus Vis. & Pančić, Goniolimon serbicum Vis., Euphorbia subhastata Vis. & Pančić, Triticum petraeum Vis. & Pančić) and one epitype (Goniolimon serbicum Vis.) are designated here.